2011
DOI: 10.1002/dc.21692
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytology of orbital meningiomas

Abstract: Meningiomas are benign tumors derived from arachnoid cells. Most commonly they arise within the cranial cavity, but they may arise extracranially in various anatomic sites. We present four cases of orbital meningiomas diagnosed on fine-needle aspiration cytology (FNAC) and confirmed on histopathology. All the cases are presented with orbital mass. FNAC smears showed classical whorling and syncytial pattern of cells, with round to oval nucleus, inconspicuous nucleoli and one each case showed intranuclear inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…To date, the cytomorphology of extracranial meningiomas has been reported predominantly via case reports in the literature [9,10,11,12,13,14,15,16,17,19,20,21,23,24,25,26,27,28]. To the best of our knowledge, this study represents the largest series detailing the cytomorphology of such tumors.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…To date, the cytomorphology of extracranial meningiomas has been reported predominantly via case reports in the literature [9,10,11,12,13,14,15,16,17,19,20,21,23,24,25,26,27,28]. To the best of our knowledge, this study represents the largest series detailing the cytomorphology of such tumors.…”
Section: Discussionmentioning
confidence: 94%
“…Previously published case reports of metastatic and primary ectopic meningiomas described tumors with typical low-grade cytomorphology [9,10,11,12,13,14,15,16,17,19,20,21,23,24,25,26,27,28]. In our study most cytology samples, particularly those from ectopic tumors, also revealed typical morphological features characteristic of low-grade intracranial meningiomas such as spindle-shaped tumor cells, whorls (concentric spheres of tumors cells), intranuclear pseudoinclusions, nuclear grooves and psammoma bodies [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients usually present with proptosis and diminution of vision. The smears show multiple whorls of meningothelial cells sometimes with intranuclear inclusions and psammomatous calcification …”
Section: Malignant Neoplasm Of Eyelidmentioning
confidence: 99%
“…[23] The smears of meningioma show multiple whorls of spindly meningothelial cells sometimes with intranuclear inclusions and psammomatous calcification. [24] The smears of neurofibroma and schwannoma show spindle cells having a wavy nucleus and a moderate amount of eosinophilic cytoplasm embedded in a fibrillary matrix.…”
Section: Discussionmentioning
confidence: 99%